What do you want to make? What to make of public library makerspaces: a look into the power of makerspaces in Singapore public libraries - Tan, Yi Lin (Nanyang Technological University, 2024)
In a 2013 article published on ALA TechSource, an imprint of the American Libraries Association (ALA), librarian C.A. Bagley defines makerspaces as “a place where people come together to create with technology”. In the same year, the ALA pointed to a feature in American Libraries magazine that contended that makerspaces are the modern-day equivalent of knitting and quilting circles and book clubs present as early as the 1870s in U.S. public libraries. In Makerspaces: Top Trailblazing Projects, Bagley (2013) investigates the relevance of makerspaces to libraries where she observes wariness on the part of librarians about getting caught up in “the flavour of the moment” (2). Ten years on, the desire by libraries to offer makerspaces shows no sign of letting up. In Singapore, in line with the Library and Archives Blueprint 2025 (LAB25), the National Library Board (NLB) opened their fourth MakeIT at Libraries at Punggol Regional Library in January 2023. Inspired by Beyond the Makerspace: Making and Relational Rhetorics (McNair, 2021), this study is a critical inquiry into the history, influencing factors, and motivations behind the genesis, adoption, and growth of public libraries makerspaces in Singapore, and the potential implications of upholding the NLB rhetoric of providing universal access to the public library makerspace and its technologies.